Parenting Styles and Their Impact on Children's Character Formation in Millennial Households in Karunrung, Makassar - Syamsidah, Syamsidah; Jusniar, Jusniar; Qurani, Besse; Amir, Syarah Syam (Indonesian Journal of Social and Educational Studies, 2024)
Abstract. This study aims to analyze the influence of parenting on character formation in millennial families in Karunrung Village, Makassar City. Using quantitative methods, this study involved 160 millennial families as a purposively selected sample. Data was collected through a closed questionnaire that measured four types of parenting: authoritarian, democratic, permissive, and disengaged. The results of the regression analysis showed that democratic parenting had a positive effect on the formation of children's character, with characteristics such as independence, responsibility, and discipline. On the contrary, permissive and uninvolved parenting has a negative effect, causing children to lack discipline and tend to have problems in self-control. In addition, the use of technology by parents moderates the influence of parenting, both positively and negatively, depending on how it is used. These findings show the importance of the role of technology and balanced parenting in shaping the character of millennial children. This study recommends the use of authoritative and controlled parenting in the context of technological advances to support the development of children's character optimally.Keywords: parenting, children's character, millennial family, technology, Makassar City.